PENGARUH PENGELOLAAN AIR TERHADAP KONSENTRASI BESI (Fe) PADA SAWAH BUKAAN BARU - Teguh Budi Prasetyo; Ruhaimah Ruhaimah; Septi Angga Wardahana (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2006)
Recently rice field in Ultisol has some problems, the most important thing is high concentration of Fe that can be toxic to the rice growth. The objective of this study was to determine the best water management to reduce concentration of Fe in recently rice field. The experiment was designed in completely randomized design with seven treatments and three replicates. The treatment consisted of continous water-logged, 1 week water-logged 1 week dried, 2 weeks water-logged 2 weeks dried, 3 weeks water-logged 3 weeks dried, 1 week dried 1 week water-logged, 2 weeks dried 2 weeks water-logged, 3 weeks dried 3 weeks water-logged. The results showed that the water management with water-logged and dried the soil could reduce Fe concentration about 720 1882 ppm. The best water management to reduce Fe concentration was 3 weeks water-logged 3 weeks dried with Fe concentration in the soil was 376 ppm. Key words : Water management, Iron, recently rice field